Peran Tutor Sebaya Dalam Upaya Menghadapi Quarter Life Crisis Di Panti Sosial Asuhan Anak (PSAA) Muhammadiyah Seyegan - Nia Handayani; Vita Purnamasari; Aisyah Nur Azizah; Raden Sugeng Riyadi (CV. Multi Kreasi Media, 2024)
Quarter Life Crisis is a phase where an emotional crisis occurs in individuals in their 20s. Emotional crises that occur in individuals during the Quarter Life Crisis phase include feelings of helplessness, feeling unsure or doubting one's own abilities, isolated and often afraid, anxious about failure in the future. The aim of this community service is to implement the role of peers to become counselors or confidants for teenagers at the Sayegan Muhammadiyah Orphanage so that the Quarter Life Crisis can be minimized. This community outreach method is by providing education about mental health and the role of peer tutors in dealing with the quater life crisis. Participants also demonstrated peer tutoring. In conclusion, in this community service, participants can apply the role of peer tutors in dealing with the quater life crisis well.